Sebaran Geografi Populasi Monyet Ekor Panjang (Macaca fascicularis) di Semenanjung Badung - Made Rahayu Kusumadewi; I Gede Soma; I Nengah Wandia (Veterinary Science and Medicine Journal, 2014)
The observational study was directed to find out the number of populations, large of habitat, home range, and density of long tailed macaques (Macaca fascicularis) in Badung Peninsula. Population site was recorded using GPS program. Data were analyzed using ArcView 3.2 and GmapCatcher programs. There were four population sites of long tailed macaques, namely Pura Dalem Karang Boma, Pura Gunung Payung, Pura Batu Pageh, and Pura Luhur Uluwatu. The average of population density was 114 individuals per hectare and the average of home range was 852,5 hectare. The study indicates that the population densities of long tailed macaques in Badung Peninsula are very high and their home ranges are very large. It is suggested that the population growth of the long tailed macaque in Badung Peninsula must be controlled for decreasing the negative impact.